INDIVIDUAL CHARACTERISTICS, WORKLOAD, AND WORK STRESS ON NURSE PERFORMANCE - Luh Gde Nita Sri Wahyuningsih; Ni Made Widnyani; Ni Luh Darmayanti (SEAN Institute, 2022)
The purpose of this study was to determine the effect of individual characteristics, workload and work stress on performance of nurses. This study used quantitative research methods. Data collection techniques used in this study was a questionnaire measuring devices in the form of Agree-Disagree Scale, in which respondents are all nurses at Kasih Ibu Hospital Denpasar many as 143 people. In this study, data analysis was performed using SEM assisted by AMOS program 22. The results of this study indicate that individual characteristics and work stress have a significant effect on the performance of nurses in Kasih Ibu Hospital Denpasar. While the workload shows no significant effect on the performance of nurses in Kasih Ibu Hospital Denpasar. From the results of this study are expected to provide an overview to the management of Kasih Ibu Hospital Denpasar in improving the performance of nurses. Increasing the performance of nurses will have an impact on service delivery to the optimal and sustainable society